Decision Analysis on Survey and SOil Investigation Problem in Power Engineering Consultant - Setyaman, Amy Maulany; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2013)
The study aims to gather and organize information for decision making against the problems arising in Power Engineering Consultantâ€™s survey and soil investigation product due to new policy in production cost efficiency that is implemented in 2012. The study conducted using Kepner and Tragoe'sÂ analytical process that consisted of four stages analytical process such as situation analysis, problem analysis, decision making analysis and potential problem analysis. As for the decision making analysis, the analysis will be conducted using Mix Method research. Starting with the qualitative method that involving detailed exploration from interview session with selected person and followed by a quantitative method, in which SMART analysis method is implemented. As the input of decision making analysis, there are five alternatives solution for Power Engineering Consultantâ€™s problem, such as: fix the problem and continue to cooperate with third party institutions, establish cooperation with external surveyor team, establish internal surveyor team, acquisition of one selected surveyor company, and establishing â€œumbrella contractâ€ with selected surveyor company. After the decision making analysis is conducted, the alternative to establishing â€œumbrella contractâ€ with selected surveyor company is selected as the best alternative solution for Power Engineering Consultantâ€™s problem. The result is considered as the best solution since the decision makers are involved in the entire decision making process. Based on this result, the implementation plan then made to be in line with Power Engineering Consultantâ€™s current conditionÂ Keywords: Problem Analysis, Decision Making Analysis, Umbrella Contract, Surveyor CompanyÂ